(untitled) (American Journal of Aquaculture and Animal Science, 2025)
The aim of this study was to investigate the influence of Talinum fruticosum leaf meal (TFLM) supplement in the diet of 24 New Zealand rabbit bucks (crosses) on their semen parameters, reproductive hormones production and selected internal organs. TFLM was incorporated into their diets at 0, 5, 10, and 15%, representing treatments (T) 1 (Control), 2, 3, and 4 respectively. After 8 weeks of exposure to the diets, data were collected, analysed and the results showed that TFLM produced no effect on semen volume, concentration, normal morphology, mortality, livability and colour, but resulted in significant rise (p<0.05) in the percentage of abnormal sperm cells (19.00, 20.00, and 15.50% in T2, T3, and T4 respectively) compared to the 11.50% found in the control group (T1). Furthermore, diets with varying levels of TFLM significantly (p<0.05) enhanced the production of Testosterone, Thyroid Stimulating Hormone (TSH), and Follicle Stimulating Hormone (FSH) in the rabbit bucks. The relative weights of the internal organs and the testicular morphometric parameters of the rabbit bucks were the same with those on the control diet, except for the kidney and left testis, which were significantly (p<0.05) heavier in rabbit bucks that received different inclusion levels of TFLM. This study concludes that Talinum fruticosum leaf meal should not be included in the diets of rabbit bucks beyond 5% to prevent impairment of semen quality.